Analisis Dampak Pembangunan Perumahan terhadap Kondisi Sosial Ekonomi Masyarakat di Kota Kandangan Kabupaten Hulu Sungai Selatan - Wardhana, Hendra Aditya; Pahlevi, Khairi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The purpose of the research is to see how the impact of housing developmenton people's socio-economic conditions in Kandangan town, Hulu Sungai Selatanregency.Data were collected by using a questionnaire method on 91 respondents by using apurposive sampling method.Result of research based on the social condition of society indicate Socialrelation between residents around residential area remains harmonious, new classemergence that resident of residence does not cause jealousy from a local citizen,local citizen feel that resident of housing also part of society exist because theywilling to follow norm together. While the impact on the community economyindicates the influence of housing development on the livelihood of the citizens issignificant, many residents who changed the profession to be workers in housing,such as a night watchman, a small trader, a housekeeper, or a security guard.Residents also feel that finding a work field becomes easier after housing. The cost ofliving tends to be the same without increasing.